Preliminary Study on pH Optimization of Biogas Production Using POME, Palm Oil Mill Effluent - joni prasetyo (Jurnal Ilmiah Teknik Kimia, 2021)
Organic waste that is not utilized will cause stinky odor. The Organic waste, especially liquid one,  has high COD. This kind Wastes with high COD are usually left not easily decomposed and those that live in the environment are anaerobic microbes which normally produce gas in metabolism. The gas usually consists of H2S and NH3 which give off an unpleasant odor. Handling of this organic waste by using a microbial source from cow dung can direct the waste conversion process to produce the main product in the form of methane (CH4). Preliminary study of liquid waste management from palm oil mill effluent (POME) in its handling. The initial conditioning was carried out by incubating cow manure and adding POME gradually by maintaining the pH of the media around 6.5. Uncontrolled treatment with a pH that did not change much from the initial pH of POME, which was between 4 - 5.5. The resulting biogas pH can reach 5.5 - 6.5 with CH4 when it is around 50%. Meanwhile, pH 6.5 - 7.5 gave the best biogas yield, namely 60%, even in the best conditions the CH4 concentration could reach 62.34% at pH 7.6.